Acute effects of voluntary isometric contractions at maximal shortening vs. ballistic stretching on flexibility, strength and jump - Hernández-Trujillo, J. Artemi; González-Rivera, María Dolores; Romero-Franco, Natalia; González-Hernández, Jorge M. (PeerJ, 2024)
Background Isometric training is used in sport, conventional physical activity and rehabilitation. Understandably, there is a great deal of research related to its effect on performance. It is known that the length of the muscle at the moment of contraction is a determinant of strength levels. In the literature we find research on isometric training in short muscle lengths, although it has not been studied in maximally shortened positions or the acute effects that occur after its application. Ballistic stretching (BS) is also popular in sport. Their execution involves actively reaching maximally shortened muscle positions. So far, isometric training has not been compared with protocols involving ballistic stretching. Considering the above, the aim of the present study was to investigate the effects of BS and voluntary isometric contraction at maximal shortening (VICAMS) on range of motion, strength and vertical jump. Methods The study involved 60 healthy, physically active individuals (40 and 52 years old) who were randomly assigned to three groups: BS, VICAMS and a control group (CG). To assess acute effects, before and after the intervention, active range of motion (AROM), maximal voluntary isometric force (MVIF) and countermovement jump height (CMJ) were determined. Results Time main effects and time*group interactions were found for all variables (p < 0.001). Between-group differences were shown for the VICAMS group after the intervention, with statistically significant higher AROM values compared to the other groups. MVIF values were also higher in the VICAMS group. Intra-group differences were observed for the VICAMS and Ballistic groups, as values on all variables increased from baseline. For the CMJ, intra-group differences showed that both the VICAMS and BS groups improved values compared to baseline values. Conclusions The application of VICAMS induced acute improvements over BS in AROM, MVIF and CMJ. These results are important for coaches seeking immediate performance improvement and offer an optimal solution to the warm-up protocol.
Keywords: Isometric training; Ballistic stretching; Shortened muscle position; Countermovement jump; AROM